Conscious sedation vs general anesthesia in pediatric dentistry – a review - Silva,Cátia Carvalho (2015)
INTRODUCTION: Performing dental treatments on pediatric patients who present behavioral problems is usually a great clinical challenge. Depending on the patients’ emotional maturity and their physical, psychological and mental skills, the usual behavior control techniques may not offer adequate efficacy and safety when dental procedures are being carried out. In these circumstances, alternative and more invasive methods such as conscious sedation and general anesthesia may become necessary. OBJECTIVE: To compare the indications and contraindications of conscious sedation and general anesthesia in pediatric dentistry. METHOD: Literature research undertaken through the MEDLINE/Pubmed, Science Direct and B-on search engines between April and June 2013 using a 5 year time frame and the following keywords: conscious sedation, general anesthesia, pediatric dentistry and guidelines. RESULTS: Conscious sedation is recommended to anxious patients who have dental and needle phobia, to patients that present an increased vomiting reflex and also to patients with special needs but capable of communicating. General anesthesia is indicated for non-cooperating patients under the age of four, in mouth breathers, in children ASA III or higher and in pediatric patients who do not communicate. CONCLUSIONS: Each technique must be selected according to the characteristics showed by patient. Although conscious sedation and general anesthesia introduce benefits to pediatric dentistry, they should not be regarded as priority intervention techniques for behavior control. The pediatric dentist’s previous knowledge of these techniques provides a better level of dental care quality as well as more safety and less discomfort for their patients.